Edital PGR/MPF nº 65, de 17 de outubro de 2019 - Jose Bonifacio Borges de Andrada (DOU, Brasília, DF, 21 out. 2019. Seção 2, p. 74., 2019)
Altera a redação do Edital PGR/MPF nº 63, de 10 de outubro de 2019.